“Wisdom Without Reflection”: constitución y costumbre en Edmund Burke - Rustighi, Lorenzo (Conceptos Históricos, 2020)
This paper addresses the key role played by the categories of “habit” and “custom” in Edmund Burke’s constitutional theory. After briefly framing the attempt to neutralize the problem of habituation in modern social contract theories (Hobbes, Rousseau, Kant), the analysis focuses on the theoretical grounds of Burke’s reappraisal of custom as a decisive component of the constitutional order. Going through a scrutiny of the notions of “imitation” and “sympathy”, which Burke develops in his 1757 Philosophical Enquiry concerning the beautiful and the sublime, the essay insists on the centrality of the dimension of heritage to the comprehension of the constitution understood not as a formal establishment of technical prerogatives but as the concrete system of relations articulated by stratified customary practices. This allows me to lay down the conditions for the interpretation of the problem of custom as the key to the constitution’s inherent plurality – which is especially illustrated in Burke’s unconventional definition of “prejudice” – thus also stressing the inseparability of such a customary social ground from the properly political process that ceaselessly reproduces the constitution as the totality of the people’s common life in virtue of effective participatory institutions.